A Rare Presentation of Mycosis Fungoides Mimicking Psoriasis Vulgaris - S. Doukaki; M. Aricò; M.R. Bongiorno (Karger Publishers, 2009)
Mycosis fungoides (MF) is an uncommon primary cutaneous lymphoma with a wide spectrum of clinicopathological manifestations. Diagnosis can be difficult in its early stages given the considerable overlap with more common benign dermatoses. We report an unusual case of MF in a 52-year-old male presenting with psoriasiform plaques on the palms and the soles who rapidly developed additional lesions on the scalp, limps and trunk. Punch biopsy of the face was obtained for routine histology and immunohistochemical stains. Chest X-ray, total body computed tomography scanning and excisional biopsy of the inguinal lymph node were performed. Review of the face biopsy revealed a diffuse dermal infiltrate containing a high number of atypical lymphocytes showing a CD3+, CD4+, CD45RO+, CD8-, CD20- immunophenotype and epidermotropism. Findings were consistent with tumor stage MF (stage IIB, T3 N1 M0). We report a rare presentation of MF mimicking psoriasis vulgaris.